Conductive paste and ceramic packaging base

By adding a specific ratio of TiO2 and Cr2O3 to the conductive paste of the ceramic packaging base to form a black conductive layer, the difficulty in identifying the conductive layer in machine vision recognition in the prior art is solved, the installation accuracy is improved and the conductive performance is maintained.

CN119786119APending Publication Date: 2025-04-08德阳三环科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510041884.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The conductive layer on the existing ceramic packaging base has difficulty in identifying the machine vision recognition process, especially in the miniaturized packaging base, which can easily lead to deviations in the installation position of the electronic components.

Method used

By introducing a specific mass ratio of TiO2 and Cr2O3 into the conductive paste, a titanium oxide film containing positive divalent titanium and positive trivalent titanium and a chromium oxide film containing positive divalent chromium are formed after sintering, so that the conductive layer appears black and is easily recognized by machine vision.

Benefits of technology

The high recognition of the conductive layer in machine vision recognition is achieved, the accuracy of electronic component installation is improved, and the excellent binding force and low resistance value of the conductive layer and the ceramic body substrate are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237200710000101
    Figure BDA0005237200710000101
  • Figure BDA0005237200710000111
    Figure BDA0005237200710000111
  • Figure BDA0005237200710000112
    Figure BDA0005237200710000112
Patent Text Reader

Abstract

The present invention belongs to the field of electronic paste, and specifically discloses a conductive paste and a ceramic packaging base; the conductive paste includes an inorganic component and an organic component; the inorganic component contains a conductive metal, TiO2 and Cr2O3; the mass ratio of TiO2 and Cr2O3 is: 1≤TiO2 / Cr2O3≤1.65. The present invention adds a specific ratio of TiO2 and Cr2O3 to the conductive paste, and after high-temperature sintering, a titanium oxide film containing positive divalent titanium and positive trivalent titanium is formed on the surface of TiO2, and a chromium oxide film containing positive divalent chromium is formed on the surface of Cr2O3, so that the conductive layer obtained by sintering the conductive paste appears black and is easy to be identified and positioned by machine vision. In addition, the bonding force between the conductive layer formed by sintering the conductive paste in the present invention and the ceramic body substrate is not less than 9N, and the resistance does not exceed 0.5Ω, and it has excellent bonding strength and conductive properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic paste, and in particular relates to a conductive paste and a ceramic packaging base. Background Art

[0002] Products such as ceramic package bases and metallized ceramic substrates are mainly used to carry electronic components such as chips and quartz crystals. During the installation of electronic components, it is usually necessary to use machine vision to identify the conductive patterns on the base or substrate for positioning, thereby ensuring the correct installation of the electronic components. The conductive layer on the existing ceramic package base is generally grayish white, which is difficult to identify during machine vision recognition, especially in miniaturized package bases, which can easily cause deviations in the installation position of electronic components. Therefore, it is necessary to provide a conductive paste that has the characteristics of being easily recognized by machine vision after being sintered into a conductive layer. Summary of the invention

[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a conductive paste.

[0004] A second object of the present invention is to provide a ceramic packaging base.

[0005] A third object of the present invention is to provide a method for preparing a ceramic packaging base.

[0006] A fourth object of the present invention is to provide application of the above conductive paste in the preparation of electronic products.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a conductive paste, comprising an inorganic component and an organic component; the inorganic component contains a conductive metal, TiO2 and Cr2O3; the mass ratio of TiO2 to Cr2O3 is: 1≤TiO2 / Cr2O3≤1.65.

[0009] The present invention introduces TiO2 and Cr2O3 into the inorganic components of the conductive paste. Chromium and titanium easily form oxides with different valence states at high temperatures, so that the color changes after sintering. When the ratio of TiO2 / Cr2O3 is in the range of 1 to 1.65, after high-temperature sintering, a titanium oxide film containing positive divalent titanium and positive trivalent titanium is formed on the surface of TiO2, and a chromium oxide film containing positive divalent chromium is formed on the surface of Cr2O3, so that the conductive layer obtained by sintering appears black. When TiO2 / Cr2O3>1.65, the conductive layer obtained by sintering the conductive paste in the present invention has poor bonding with the ceramic body substrate, and the pores of the conductive layer after sintering increase, so that the conductivity is reduced; when TiO2 / Cr2O3<1, the saturation of the conductive layer obtained by sintering the conductive paste in the present invention cannot meet the requirements, the color is gray, and it is not easy to be recognized by machine vision.

[0010] In some embodiments of the present invention, the mass ratio of TiO2 and Cr2O3 (i.e., TiO2 / Cr2O3) can be any value of 1, 1.02, 1.04, 1.06, 1.08, 1.1, 1.12, 1.14, 1.16, 1.18, 1.2, 1.22, 1.24, 1.26, 1.28, 1.3, 1.32, 1.34, 1.36, 1.38, 1.4, 1.42, 1.44, 1.46, 1.47, 1.48, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.62, 1.64, 1.65, or a range formed by any two of them.

[0011] In some embodiments of the present invention, the mass ratio of the organic component to the inorganic component is (0.15-0.4):1; in some embodiments of the present invention, the mass ratio of the organic component to the inorganic component is 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.2:1, 0.22:1, 0.24:1, 0.25:1, 0.26:1, 0.28:1, 0.3:1, 0.32:1, 0.34:1, 0.36:1, 0.37:1, 0.38:1, 0.4:1, any one of the values ​​or a range value formed by any two of them.

[0012] In some embodiments of the present invention, the inorganic component includes conductive metals, Al2O3, SiO2, MgO, CaO, TiO2, Cr2O3.

[0013] In some embodiments of the present invention, taking the total mass percentage of inorganic components as 100%, the inorganic components include the following components in mass percentage: conductive metal 70-89%, Al2O3 6-11%, SiO2 1-5%, MgO 1-4%, CaO 1-4%, TiO2 1-5%, and Cr2O3 1-5%.

[0014] In some embodiments of the present invention, the mass percentage of the conductive metal can be 70%, 70.5%, 71%, 72%, 73%, 73.5%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 82.1%, 83%, 84%, 85%, 86%, 87%, 88%, 88.7%, 89%, any one of the values ​​or a range formed by any two of them.

[0015] In some embodiments of the present invention, the conductive metal is selected from at least one of W, Mo, Mn, Cu, Ni, Ag, and Au.

[0016] In some embodiments of the present invention, the average particle size of the conductive metal is 1.2 to 3.5 μm; in some embodiments of the present invention, the average particle size of the conductive metal may be any value among 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.5 μm, or a range formed by any two of them.

[0017] In some embodiments of the present invention, the mass percentage of Al2O3 can be any value of 6%, 6.5%, 7%, 7.5%, 8%, 8.1%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11% or a range formed by any two of them.

[0018] In some embodiments of the present invention, the average particle size of the Al2O3 is 0.5-2.2 μm; in some embodiments of the present invention, the average particle size of the Al2O3 can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, any one of the values ​​or a range formed by any two of them.

[0019] In some embodiments of the present invention, the mass percentage of SiO2 can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, any one of the values ​​or a range formed by any two of them.

[0020] In some embodiments of the present invention, the average particle size of the SiO2 is 0.5-2.2 μm; in some embodiments of the present invention, the average particle size of the SiO2 can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, any one of the values ​​or a range formed by any two of them.

[0021] In some embodiments of the present invention, the mass percentage of MgO can be any value of 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4% or a range formed by any two of them.

[0022] In some embodiments of the present invention, the average particle size of the MgO is 0.5-2.2 μm; in some embodiments of the present invention, the average particle size of the MgO may be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, any one of the values ​​or a range formed by any two of them.

[0023] In some embodiments of the present invention, the mass percentage of CaO can be any value of 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4% or a range formed by any two of them.

[0024] In some embodiments of the present invention, the average particle size of the CaO is 0.5-2.2 μm; in some embodiments of the present invention, the average particle size of the CaO can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, any one of the values ​​or a range formed by any two of them.

[0025] In some embodiments of the present invention, the mass percentage of TiO2 can be 1%, 1.1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.5%, 3.6%, 3.8%, 3.82%, 4%, 4.08%, 4.2%, 4.36%, 4.4%, 4.6%, 4.8%, 5%, any one of the values ​​or a range formed by any two of them.

[0026] In some embodiments of the present invention, the average particle size of TiO2 is 0.5-2.2 μm; in some embodiments of the present invention, the average particle size of TiO2 can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, any one of the values ​​or a range formed by any two of them.

[0027] In some embodiments of the present invention, the mass percentage of Cr2O3 can be any value among 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, or a range formed by any two of them.

[0028] In some embodiments of the present invention, the average particle size of the Cr2O3 is 0.5-2.2 μm; in some embodiments of the present invention, the average particle size of the Cr2O3 can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, any one of the values ​​or a range formed by any two of them.

[0029] In some embodiments of the present invention, the organic component includes resin, organic solvent, organic additive.

[0030] In some embodiments of the present invention, taking the total mass percentage of organic components as 100%, the organic components include the following components in mass percentages: 5-20% resin, 70-90% organic solvent, and 1-10% organic additive.

[0031] In some embodiments of the present invention, the mass percentage of the resin can be any value of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range formed by any two of them.

[0032] In some embodiments of the present invention, the resin is selected from at least one of polyethylene resin, polypropylene resin, ethyl cellulose, polyurethane, polyimide, and epoxy resin.

[0033] In some embodiments of the present invention, the mass percentage of the organic solvent can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or any value in the range formed by any two of them.

[0034] In some embodiments of the present invention, the organic solvent is selected from at least one of terpineol, butyl carbitol, diethyl phthalate, and tributyl citrate.

[0035] In some embodiments of the present invention, the mass percentage of the organic additive may be any one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range formed by any two of them.

[0036] In some embodiments of the present invention, the organic additive is selected from at least one of Span, JA-281 and dimethylformamide. JA-281 is a commercially available product, the main component of which is an aqueous solution of ammonium salt of a copolymer of acrylic acid and methacrylic acid.

[0037] In some embodiments of the present invention, the conductive paste is prepared by a preparation method comprising the following steps: grinding an inorganic component and mixing the resultant with an organic component to obtain the conductive paste.

[0038] In some embodiments of the present invention, the grinding time is 12 to 16 hours.

[0039] In some embodiments of the present invention, the mixing is performed by at least one of grinding and kneading.

[0040] In some embodiments of the present invention, the conductive paste is prepared by a preparation method comprising the following steps: mixing and grinding the inorganic component and acetone, then mixing and grinding with the resin, filtering and mixing to remove the acetone, and then mixing with the remaining components of the organic component to obtain the conductive paste.

[0041] The second aspect of the present invention provides a ceramic packaging base, comprising a ceramic body and a conductive layer arranged on the ceramic body; the conductive layer is made of the conductive paste described in the first aspect of the present invention; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium.

[0042] In some embodiments of the present invention, the ratio of the mass of the divalent chromium to the total mass of the divalent titanium and the trivalent titanium is: 0.15≤Cr 2+ / (Ti 2+ +Ti 3+ )≤0.65; In some embodiments of the present invention, the ratio of the mass of the divalent chromium to the total mass of the divalent titanium and trivalent titanium (i.e., Cr 2+ / (Ti 2+ +Ti 3+ )) can be any one of 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.61, 0.63, 0.65, or a range formed by any two of them. In some preferred embodiments of the present invention, the ratio of the mass of the divalent chromium to the total mass of the divalent titanium and the trivalent titanium is: 0.2≤Cr 2+ / (Ti 2+ +Ti 3+ )≤0.6. When Cr 2+ / (Ti 2+ +Ti 3+ ) is 0.15-0.65, the black saturation value of the conductive layer is low, easy to be recognized by machine vision, and the bonding force and resistance value also meet the use requirements; when Cr 2+ / (Ti 2+ +Ti 3 + ) is 0.2-0.6, the black saturation value of the conductive layer is lower, the color of the conductive layer appears darker, and the bonding strength between the conductive layer and the base ceramic layer is better, making it easier to be recognized by machine vision. 2+ / (Ti 2+ +Ti 3+ ) ratio is less than 0.15, the binding force is reduced; if Cr 2+ / (Ti 2+ +Ti 3+ ) is greater than 0.65, the black saturation of the conductive layer deteriorates.

[0043] In some embodiments of the present invention, the ratio of the mass of the divalent titanium to the mass of the trivalent titanium is: 0.55≤Ti 2+ / Ti 3+ ≤1.1. In some embodiments of the present invention, the ratio of the mass of divalent titanium to the mass of trivalent titanium (i.e., Ti 2+ / Ti 3+ ) is 0.55, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.75, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1.0, 1.1, or a range formed by any two of the values. In some preferred embodiments of the present invention, the ratio of the mass of the divalent titanium to the mass of the trivalent titanium is: 0.6≤Ti 2+ / Ti 3+ ≤1. When Ti 2+ / Ti 3+ When the mass ratio of Ti is 0.55-1.1, the black saturation value of the conductive layer is low, the bonding force and resistance value meet the requirements, and it is easy to be recognized by machine vision. 2+ / Ti 3+ When the mass ratio is between 0.6 and 1, the black saturation value of the conductive layer is lower, the color of the conductive layer appears darker, and the bonding force is stronger, making it easier to be recognized by machine vision.

[0044] In some embodiments of the present invention, the ratio of the mass of the tetravalent titanium to the total mass of the divalent titanium and the trivalent titanium is: 0.98≤Ti 4+ / (Ti 2+ +Ti 3+ )≤1.9. In some embodiments of the present invention, the ratio of the mass of the tetravalent titanium to the total mass of the divalent titanium and the trivalent titanium (Ti 4+ / (Ti 2+ +Ti 3+ )) can be any value among 0.98, 1.0, 1.1, 1.2, 1.3, 1.38, 1.4, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.5, 1.6, 1.66, 1.7, 1.8, 1.9 or a range formed by any two of them. In some preferred embodiments of the present invention, the ratio of the mass of the tetravalent titanium to the total mass of the divalent titanium and the trivalent titanium is: 1≤Ti 4+ / (Ti2+ +Ti 3+ )≤1.8. When Ti 4+ / (Ti 2+ +Ti 3+ ) is 0.98-1.9, the bonding force of the conductive layer is better, meeting the use requirements, and the black saturation value of the conductive layer is low, which is easy to be recognized by machine vision. 4+ / (Ti 2+ +Ti 3+ ) is 1 to 1.8, the bonding strength of the conductive layer can be further improved, thereby obtaining a conductive layer with excellent bonding strength that can be identified by machine vision.

[0045] In some embodiments of the present invention, the conductive layer contains the following elements in percentage by mass: 6% to 11% Al element calculated as Al2O3, 1% to 5% Si element calculated as SiO2, 1% to 4% Mg element calculated as MgO, 1% to 4% Ca element calculated as CaO, 1% to 5% Ti element calculated as TiO2, 1% to 5% Cr element calculated as Cr2O3, and 70% to 89% of at least one conductive metal element selected from W, Mo, Mn, Cu, Ni, Ag, and Au.

[0046] In some embodiments of the present invention, the saturation of the conductive layer is ≤ 1.5. In some preferred embodiments of the present invention, the saturation of the conductive layer is ≤ 1.0; in some preferred embodiments of the present invention, the saturation of the conductive layer is ≤ 0.6.

[0047] In some embodiments of the present invention, the resistance of the conductive layer is ≤ 0.5Ω. In some preferred embodiments of the present invention, the resistance of the conductive layer is ≤ 0.4Ω.

[0048] In some embodiments of the present invention, the binding force of the conductive layer is ≥ 9 N. In some preferred embodiments of the present invention, the binding force of the conductive layer is ≥ 10 N.

[0049] The second aspect of the present invention provides a method for preparing the ceramic package base according to the first aspect of the present invention, comprising the following steps:

[0050] The conductive slurry described in the first aspect of the present invention is used to prepare a conductive layer on a ceramic green body, and then the layers are stacked to obtain a ceramic package base green body;

[0051] The ceramic package base green body is sintered to obtain the ceramic package base.

[0052] In some embodiments of the present invention, the ceramic green body is made by using ceramic slurry, which is a common slurry for ceramic package base ceramic bodies in the art.

[0053] In some embodiments of the present invention, the sintering temperature of the sintering step is 1200-1700°C; in some embodiments of the present invention, the sintering temperature of the sintering step can be any value among 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, 1700°C or a range formed by any two of them.

[0054] In some embodiments of the present invention, the sintering atmosphere of the sintering step is an inert gas or a mixture of an inert gas and hydrogen. In some embodiments of the present invention, the inert gas is selected from at least one of nitrogen and argon.

[0055] In some embodiments of the present invention, the sintering atmosphere in the sintering step is a mixed gas of nitrogen and hydrogen in a volume ratio of (6-4):3.

[0056] In some embodiments of the present invention, the heating rate of the sintering step is 0.8-2.5°C / min; in some embodiments of the present invention, the heating rate of the sintering step is 0.8°C / min, 0.9°C / min, 1°C / min, 1.1°C / min, 1.2°C / min, 1.3°C / min, 1.4°C / min, 1.5°C / min, 1.6°C / min, 1.7°C / min, 1.8°C / min, 1.9°C / min, 2°C / min, 2.1°C / min, 2.2°C / min, 2.3°C / min, 2.4°C / min, 2.5°C / min, any one of the values ​​or a range formed by any two of them.

[0057] In some embodiments of the present invention, the sintering time of the sintering step is 16 to 20 hours; in some embodiments of the present invention, the sintering time of the sintering step is any one of 16 hours, 17 hours, 18 hours, 19 hours, and 20 hours, or a range formed by any two of them.

[0058] The present invention realizes the regulation of the valence change of Ti and Cr elements by regulating the sintering temperature, sintering time and sintering heating rate.

[0059] The second aspect of the present invention provides use of the conductive paste described in the first aspect of the present invention in the preparation of electronic products.

[0060] The beneficial effects of the present invention are as follows: by adding TiO2 and Cr2O3 in a specific mass ratio to the conductive paste, after the conductive paste is sintered at a high temperature, a titanium oxide film containing positive divalent titanium and positive trivalent titanium is formed on the surface of TiO2, and a chromium oxide film containing positive divalent chromium is formed on the surface of Cr2O3, so that the conductive layer obtained by sintering the conductive paste appears black and is easy to be identified and positioned by machine vision. In addition, the conductive layer formed by sintering the conductive paste in the present invention has excellent bonding strength with the ceramic body substrate, the bonding force is not less than 9N, and has excellent conductive properties, and the resistance does not exceed 0.5Ω. DETAILED DESCRIPTION

[0061] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0062] The average particle size of the conductive metal powder (i.e., tungsten powder) used in the embodiments and comparative examples of the present invention is 2.1 μm; the average particle size range of each oxide powder (i.e., SiO2, Al2O3, MgO, CaO, TiO2, Cr2O3) is 1.5 μm.

[0063] The type and mass proportion of each element in the conductive layer in the embodiments of the present invention and the comparative examples can be obtained by XRF detection; the mass of each valence element in the conductive layer can be obtained by XPS (X-ray photoelectron spectroscopy), mass spectrometry, atomic absorption spectroscopy and the like.

[0064] Example 1

[0065] This example provides a ceramic package base, which includes a ceramic body and a conductive layer disposed on the ceramic body; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium, wherein the mass ratio of divalent titanium to trivalent titanium (i.e., Ti 2+ / Ti 3+ ) is 0.78; the ratio of the mass of divalent chromium to the total mass of divalent titanium and trivalent titanium (i.e. Cr 2+ / (Ti 2+ +Ti 3+ )) is 0.48; the mass of tetravalent titanium: the ratio of the total mass of divalent titanium and trivalent titanium (i.e. Ti 4+ / (Ti 2+ +Ti 3+ )) is 1.45, as shown in Table 1.

[0066] The conductive layer in this example is formed by sintering a conductive paste; the conductive paste is composed of an inorganic component and an organic component, and the ratio between the mass of the organic component and the mass of the inorganic component (i.e., the organic component / inorganic component) is 0.25; the inorganic component is composed of the following components in mass percentage: W 76%, SiO2 2%, Al2O3 10%, MgO 2%, CaO 3%, TiO23.5%, Cr2O3 3.5%, and the ratio between the mass of TiO2 and the mass of Cr2O3 (i.e., TiO2 / Cr2O3) is 1; the organic component is composed of the following components in mass percentage: resin (ethyl cellulose) 10%, solvent (pinene alcohol) 85%, and organic additive (dimethylformamide) 5%, see the formula of the inorganic component in Table 2 and the formula of the organic component in Table 3 for details.

[0067] The ceramic package base in this example is prepared by a preparation method comprising the following steps:

[0068] (1) Mix the formulated amount of tungsten powder, various oxide powders (i.e., SiO2, Al2O3, MgO, CaO, TiO2, Cr2O3), and acetone and ball mill for 12 hours. The speed of the mixed ball mill is 80 rpm, and the mass ratio of the powder (i.e., tungsten powder and various oxide powders) to acetone is 1:0.5;

[0069] (2) Then add some ethyl cellulose resin and ball mill for 6 hours;

[0070] (3) filtering with an 800-mesh filter, placing the filtrate in a mixer for preliminary mixing to remove acetone;

[0071] (4) adding an organic additive, the remaining ethyl cellulose resin, and a solvent and kneading the mixture for 4 hours to obtain a conductive paste.

[0072] (5) processing the ceramic slurry into a ceramic green body;

[0073] (6) processing the ceramic green body into a desired structure according to the structural requirements of different ceramic layers in the package base and the pattern requirements of the conductive layer, and printing the conductive layer on the ceramic green body using the conductive paste in this example;

[0074] (7) stacking the ceramic green sheets obtained in step (6) to form a ceramic package base green sheet;

[0075] (8) The ceramic package base green body was sintered in a nitrogen atmosphere at a sintering temperature of 1460° C., a heating rate of 1.5° C. / min, and a sintering time of 18 h (the sintering parameters are shown in Table 4), thereby obtaining the ceramic package base in this example.

[0076] Embodiments 2 to 4

[0077] The ceramic package bases in Examples 2 to 4 differ from the ceramic package base in Example 1 only in that:

[0078] (1) The mass ratios of the valence elements in the conductive layer are different, as shown in Table 1;

[0079] (2) The mass percentages of TiO2 and Cr2O3 in the conductive paste used are different, and the mass ratios of TiO2 / Cr2O3 are different, as shown in Table 2.

[0080] The preparation method of the ceramic package base in Examples 2 to 4 is the same as the preparation method of the ceramic package base in Example 1.

[0081] Embodiments 5 to 9

[0082] The difference between the ceramic package bases in Examples 5 to 9 and the ceramic package base in Example 2 is that the mass ratios of the valence elements in the conductive layer are different, as shown in Table 1.

[0083] The difference between the preparation methods of the ceramic package base in Examples 5 to 9 and the preparation method of the ceramic package base in Example 2 is only that the sintering temperature, the heating rate and the sintering time are different, as shown in Table 4.

[0084] Example 10

[0085] This example provides a ceramic package base, which includes a ceramic body and a conductive layer disposed on the ceramic body; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium, wherein the mass ratio of divalent titanium to trivalent titanium (i.e., Ti 2+ / Ti 3+ ) is 0.84; the ratio of the mass of divalent chromium to the total mass of divalent titanium and trivalent titanium (i.e. Cr 2+ / (Ti 2+ +Ti 3+ )) is 0.33; the mass of tetravalent titanium: the ratio of the total mass of divalent titanium and trivalent titanium (i.e. Ti 4+ / (Ti 2+ +Ti 3+ )) is 1.2, as shown in Table 1.

[0086] The conductive layer in this example is formed by sintering a conductive paste; the conductive paste is composed of an inorganic component and an organic component, and the ratio between the mass of the organic component and the mass of the inorganic component (i.e., the organic component / inorganic component) is 0.37; the inorganic component is composed of the following components in mass percentage: W 70.5%, SiO2 5%, Al2O3 6.5%, MgO 4%, CaO 4%, TiO2 5%, Cr2O3 5%, and the ratio between the mass of TiO2 and the mass of Cr2O3 (i.e., TiO2 / Cr2O3) is 1; the organic component is composed of the following components in mass percentage: resin (polyethylene resin) 5%, solvent (butyl carbitol) 88%, and organic additive (span) 7%, see the formula of the inorganic component in Table 2 and the formula of the organic component in Table 3 for details.

[0087] The preparation method of the ceramic package base in this example is different from the preparation method of the ceramic package base in Example 1 only in that the sintering atmosphere in step (8) of this example is a mixture of nitrogen and hydrogen in a volume ratio of 5:3, as shown in Table 4.

[0088] Embodiment 11

[0089] This example provides a ceramic package base, which includes a ceramic body and a conductive layer disposed on the ceramic body; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium, wherein the mass ratio of divalent titanium to trivalent titanium (i.e., Ti 2+ / Ti 3+ ) is 0.78; the ratio of the mass of divalent chromium to the total mass of divalent titanium and trivalent titanium (i.e. Cr 2+ / (Ti 2+ +Ti 3+ )) is 0.5; the mass of tetravalent titanium: the ratio of the total mass of divalent titanium and trivalent titanium (i.e. Ti 4+ / (Ti 2+ +Ti 3+ )) is 1.42, as shown in Table 1.

[0090] The conductive layer in this example is formed by sintering a conductive paste; the conductive paste is composed of an inorganic component and an organic component, and the ratio between the mass of the organic component and the mass of the inorganic component (i.e., the organic component / inorganic component) is 0.32; the inorganic component is composed of the following components in mass percentage: W 82.1%, SiO2 1.2%, Al2O3 11%, MgO 1%, CaO 1%, TiO2 2.2%, Cr2O3 1.5%, and the ratio between the mass of TiO2 and the mass of Cr2O3 (i.e., TiO2 / Cr2O3) is 1.47; the organic component is composed of the following components in mass percentage: resin (polyurethane) 20%, solvent (diethyl phthalate) 70%, and organic additive (JA-281, purchased from Tianjin Xiens Biochemical Technology Co., Ltd., whose main component is: an aqueous solution of ammonium salt of a copolymer of acrylic acid and methacrylic acid) 10%, see the formula of the inorganic component in Table 2 and the formula of the organic component in Table 3 for details.

[0091] The preparation method of the ceramic package base in this example is different from the preparation method of the ceramic package base in Example 1 only in that the sintering atmosphere in step (8) of this example is a mixture of nitrogen and hydrogen in a volume ratio of 5:3, the sintering temperature is 1290°C, and the heating rate is 2.2°C / min, as shown in Table 4.

[0092] Example 12

[0093] This example provides a ceramic package base, which includes a ceramic body and a conductive layer disposed on the ceramic body; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium, wherein the mass ratio of divalent titanium to trivalent titanium (i.e., Ti 2+ / Ti 3+ ) is 1; the mass of divalent chromium: the ratio of the total mass of divalent titanium and trivalent titanium (i.e. Cr 2+ / (Ti 2+ +Ti 3+ )) is 0.44; the mass of tetravalent titanium: the ratio of the total mass of divalent titanium and trivalent titanium (i.e. Ti 4+ / (Ti 2+ +Ti 3+ )) is 1.38, as shown in Table 1.

[0094] The conductive layer in this example is formed by sintering a conductive paste; the conductive paste is composed of an inorganic component and an organic component, and the ratio between the mass of the organic component and the mass of the inorganic component (i.e., the organic component / inorganic component) is 0.17; the inorganic component is composed of the following components in mass percentage: W 88.7%, SiO2 1%, Al2O3 6%, MgO 1.2%, CaO 1%, TiO2 1.1%, Cr2O3 1%, and the ratio between the mass of TiO2 and the mass of Cr2O3 (i.e., TiO2 / Cr2O3) is 1.10; the organic component is composed of the following components in mass percentage: resin (polyimide) 15%, solvent (tributyl citrate) 83.5%, and organic additive (dimethylformamide) 1.5%, see the formula of the inorganic component in Table 2 and the formula of the organic component in Table 3 for details.

[0095] The preparation method of the ceramic package base in this example is different from the preparation method of the ceramic package base in Example 1 only in that the sintering temperature in step (8) of this example is 1540°C, the heating rate is 1.4°C / min, and the sintering time is 20h, as shown in Table 4.

[0096] Embodiment 13

[0097] This example provides a ceramic package base, which includes a ceramic body and a conductive layer disposed on the ceramic body; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium, wherein the mass ratio of divalent titanium to trivalent titanium (i.e., Ti 2+ / Ti 3+ ) is 0.8; the ratio of the mass of divalent chromium to the total mass of divalent titanium and trivalent titanium (i.e. Cr 2+ / (Ti 2+ +Ti 3+ )) is 0.2; the mass of tetravalent titanium: the ratio of the total mass of divalent titanium and trivalent titanium (i.e. Ti 4+ / (Ti 2+ +Ti 3+ )) is 1.66, as shown in Table 1.

[0098] The conductive layer in this example is formed by sintering a conductive paste; the conductive paste is composed of an inorganic component and an organic component, and the ratio between the mass of the organic component and the mass of the inorganic component (i.e., the organic component / inorganic component) is 0.22; the inorganic component is composed of the following components in mass percentage: W 73.5%, SiO2 3.4%, Al2O3 8.1%, MgO 3%, CaO2.2%, TiO2 5%, Cr2O3 4.8%, and the ratio between the mass of TiO2 and the mass of Cr2O3 (i.e., TiO2 / Cr2O3) is 1.04; the organic component is composed of the following components in mass percentage: resin (epoxy resin) 13%, solvent (pinene alcohol) 78.5%, and organic additive (dimethylformamide) 8.5%, see the formula of the inorganic component in Table 2 and the formula of the organic component in Table 3 for details.

[0099] The preparation method of the ceramic package base in this example is different from the preparation method of the ceramic package base in Example 1 only in that the sintering atmosphere in step (8) of this example is a mixture of nitrogen and hydrogen in a volume ratio of 5:3, the sintering temperature is 1680°C, and the heating rate is 0.9°C / min, as shown in Table 4.

[0100] Comparative Examples 1-2

[0101] The ceramic package bases in Comparative Examples 1 and 2 differ from the ceramic package base in Example 1 only in that:

[0102] (2) The mass ratios of the valence elements in the conductive layer are different, as shown in Table 1;

[0103] (2) The mass percentages of TiO2 and Cr2O3 in the conductive paste used are different, and the mass ratios of TiO2 / Cr2O3 are different, as shown in Table 2.

[0104] The preparation method of the ceramic package base in Comparative Examples 1-2 is the same as the preparation method of the ceramic package base in Example 1.

[0105] Table 1 Mass ratio of each valence element in the conductive layer

[0106]

[0107]

[0108] Table 2 Formula of inorganic components of conductive paste

[0109]

[0110]

[0111] Table 3 Formulation of organic components of conductive paste

[0112]

[0113] Table 4 Sintering process parameters

[0114]

[0115]

[0116] Performance Testing

[0117] The color, saturation, conductive layer bonding force and resistance value of the conductive layer of the ceramic package bases prepared in Examples 1 to 13 and Comparative Examples 1 to 2 were tested respectively. The specific testing methods are as follows:

[0118] (1) Conductive layer color and saturation:

[0119] Use a spectrophotometer to measure the CIE Lab* value of the conductive layer, and then use the saturation calculation formula The saturation S is calculated.

[0120] When S < 0.6, the black saturation is excellent;

[0121] When 0.6≤S≤1.5, the black saturation meets the standard;

[0122] When S>1.5, the color of the conductive layer is gray and does not meet the standard.

[0123] (2) Conductive layer bonding strength:

[0124] The metal ring is soldered to the conductive layer using silver-copper solder, and a tensile test is performed until the two are completely separated. The tensile force value is the bonding strength.

[0125] The bonding force is required to be ≥9N to be qualified. The bonding force is ≥11N to be excellent.

[0126] (3) Conductivity of the conductive layer (resistance value):

[0127] A conductive layer with a length, width and thickness of 20mm*20mm*(20-25μm) is printed on alumina ceramics, and then its resistance value R is tested using a digital bridge.

[0128] Requirement: R≤0.5Ω.

[0129] The performance data of the ceramic package bases prepared in Examples 1 to 13 and Comparative Examples 1 to 2 measured according to the above test method are shown in Table 5 below.

[0130] Table 5 Performance data of ceramic package base

[0131] Saturation Resistance R(Ω) Binding force (N) Example 1 0.41 0.32 11 Example 2 0.48 0.35 12.3 Example 3 0.5 0.37 13.5 Example 4 0.55 0.4 14 Example 5 0.6 0.34 9.8 Example 6 0.81 0.33 10.2 Example 7 0.57 0.35 9.3 Example 8 1.16 0.34 9.7 Example 9 1.45 0.34 9.1 Example 10 0.47 0.4 12.8 Embodiment 11 0.55 0.3 11.2 Example 12 0.5 0.14 11.9 Embodiment 13 0.56 0.28 11.1 Comparative Example 1 1.88 0.24 10.1 Comparative Example 2 0.72 0.61 8.3

[0132] As shown in Table 5, the ceramic package bases in Examples 1 to 13 of the present invention are formed with a titanium oxide film containing positive divalent titanium and positive trivalent titanium on the surface of TiO2 after sintering at a high temperature of 1200°C-1700°C, and a chromium oxide film containing positive divalent chromium is formed on the surface of Cr2O3, so that the sintered conductive layer appears black, that is, the saturation is not higher than 1.5, so that it is easy to be identified and positioned by machine vision, and the installation accuracy of electronic components is improved. In addition, the bonding force of the ceramic package bases in Examples 1 to 13 of the present invention is greater than 9N, and the resistance is not higher than 0.5Ω, which meets the use requirements of the ceramic package base. Compared with Example 1, the TiO2 content in the conductive paste of Comparative Example 1 is relatively low, and the obtained ceramic package base has a recognition degree higher than 1.88 and is grayish in color. It is difficult to be identified and positioned by machine vision during electronic component installation, and the electronic component installation accuracy is not high. The TiO2 content in the conductive paste of Comparative Example 2 is relatively high, and the conductive layer of the ceramic package base obtained after sintering has poor bonding strength with the base ceramic body, and the porosity of the conductive layer is increased, which reduces the conductivity.

[0133] In summary, the present invention adds TiO2 and Cr2O3 in a specific mass ratio into the conductive paste. After high-temperature sintering at 1200℃-1700℃, a titanium oxide film containing divalent titanium and trivalent titanium is formed on the surface of TiO2, and a chromium oxide film containing divalent chromium is formed on the surface of Cr2O3, so that the sintered conductive layer appears black and can be easily identified and positioned by machine vision.

[0134] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A conductive paste, characterized in that: It comprises inorganic components and organic components; the inorganic components contain conductive metal, TiO2 and Cr2O3; the mass ratio of TiO2 to Cr2O3 is: 1≤TiO2 / Cr2O3≤1.

65.

2. The conductive paste according to claim 1, characterized in that: The mass ratio of the organic component to the inorganic component is (0.15-0.4):

1.

3. The conductive paste according to claim 1 or 2, characterized in that: Taking the total mass percentage of the inorganic components as 100%, the inorganic components include the following components in mass percentage: conductive metal 70-89%, Al2O3 6-11%, SiO2 1-5%, MgO 1~4%, CaO 1~4%, TiO2 1~5%, Cr2O3 1~5%; And / or, taking the total mass percentage of the organic components as 100%, the organic components include the following components in mass percentages: 5-20% of resin, 70-90% of organic solvent, and 1-10% of organic additives.

4. The conductive paste according to claim 3, characterized in that: The conductive metal is selected from at least one of W, Mo, Mn, Cu, Ni, Ag, and Au; And / or, the resin is selected from at least one of polyethylene resin, polypropylene resin, ethyl cellulose, polyurethane, polyimide, and epoxy resin; And / or, the organic solvent is selected from at least one of terpineol, butyl carbitol, diethyl phthalate, and tributyl citrate; And / or, the organic additive is selected from at least one of Span, JA-281 and dimethylformamide.

5. A ceramic package base, characterized in that: It comprises a ceramic body and a conductive layer arranged on the ceramic body; the conductive layer is made of the conductive paste according to any one of claims 1 to 4; the conductive layer contains divalent titanium, trivalent titanium, tetravalent titanium and divalent chromium.

6. The ceramic package base according to claim 5, characterized in that: The ratio of the mass of the divalent chromium to the total mass of the divalent titanium and the trivalent titanium is: 0.15≤Cr 2+ / (Ti 2+ +Ti 3+ )≤0.65; And / or, the ratio of the mass of the divalent titanium to the mass of the trivalent titanium is: 0.55≤Ti 2+ / Ti 3+ ≤1.1; And / or, the ratio of the mass of the tetravalent titanium to the total mass of the divalent titanium and the trivalent titanium is: 0.98≤Ti 4+ / (Ti 2+ +Ti 3+ )≤1.

9.

7. The ceramic package base according to claim 5, characterized in that: The saturation of the conductive layer is ≤1.5; And / or, the resistance of the conductive layer is ≤0.5Ω; And / or, the binding force of the conductive layer is ≥9N.

8. The method for preparing a ceramic package base according to any one of claims 5 to 7, characterized in that: The following steps are involved: Using the conductive paste described in any one of claims 1 to 4 to prepare a conductive layer on a ceramic green body, and then laminating to obtain a ceramic package base green body; The ceramic package base green body is sintered to obtain the ceramic package base.

9. The method for preparing a ceramic package base according to claim 8, characterized in that: The sintering step has at least one of the following characteristics: (a) The sintering temperature is 1200-1700°C; (b) The sintering atmosphere is an inert gas or a mixture of an inert gas and hydrogen; (c) Heating rate is 0.8 to 2.5 °C / min; (d) The sintering time is 16 to 20 hours.

10. Use of the conductive paste according to any one of claims 1 to 4 in the preparation of electronic products.